EFISIENSI KINERJA PEMBINA MELALUI MANAJEMEN SUMBER DAYA MANUSIA STUDI PESANTREN MODERN MUHAMMADIYAH BOARDING SCHOOL PALOPO - Sulfiani; Muhammad Ghozali; Nur Saidah (LP2M IAIN Sultan Amai Gorontalo, 2023)
Abstrack The success of educational institutions depends on the quality of their resources, including teaching and educational staff which are managed in a measurable manner and must enforce good cooperation, motivate each other with peers, and provide ideas that can improve performance in order to build the competence of pesantren supervisors. This study aims to determine the development of the supervisor's performance through human resource management in the MBS Palopo modern Islamic boarding school. This type of research uses qualitative descriptive approach. Data collection was carried out through observation and interview techniques with the director of the pesantren, supervisors and educators of the pesantren located at the Modern Muhammadiyah Boarding School (MBS) Palopo Islamic Boarding School. The results of the study show that the development of the supervisor's performance at the MBS Palopo Islamic boarding school is first, education and training. The MBS Palopo Islamic Boarding School provides education and training to coaches as a form of development and adjustment to their duties. The training is conducted both online and offline and covers various aspects such as learning methodology and improving language skills. Second, mutation. The MBS Palopo Islamic Boarding School carried out a mutation in order to provide opportunities and motivate the coaches. With mutations, coaches can develop themselves and learn new things and experience challenges in different assignments. Third, facilitation and motivation. The MBS Palopo Islamic Boarding School provides facilities to supervisors to improve the quality of performance. These facilities include support in procuring teaching materials, technology facilities, as well as regular coaching and supervision. With the efforts to develop the performance of the supervisors, it is hoped that the supervisors can improve the quality of performance in managing Islamic boarding schools and make a positive contribution to the progress of these educational institutions.